Revision of southern African species of the anglerfish genus Chaunax (Lophiiformes: Chaunacidae), with descriptions of three new species - Ho, Hsuan-Ching; Ma, Wen-Chun (Zootaxa, 2016)
Species of the anglerfish genus Chaunax occurring off southern Africa are reviewed and nine species are recognized: C. africanus, C. apus, C. flammeus, C. penicillatus, C. russatus, C. suttkusi, and three newly described species. Chaunax atimovatae sp. nov. is distinguished by having numerous tiny melanophores on the skin and a mixture of bifurcate and simple spinules on its dorsal surface, scattered rounded green spots circled by yellow on its dorsal surface, 9 or 10 rakers on the second gill arch, and 2 neuromasts in the upper preopercular, 11–14 in the pectoral, 31–37 in the lateral-line proper. Chaunax heemstraorum sp. nov. is distinguished by a combination of all dermal spinules simple, large green spots on the dorsal surface, 10–12 rakers on the second gill arch; and 3 neuromasts in the upper preopercular, 13–18 in the pectoral, 37–42 in the lateral-line proper, and usually 5 on the caudal-fin base. Chaunax hollemani sp. nov. is distinguished by cirri on top of the head, head width 16.0–18.5% SL, pre-preopercle length 26.8–28.5% SL, 9 rakers on the second gill arch, and 2 neuromasts in the upper preopercular, 11–14 in the pectoral, and 33–38 in the lateral-line proper. A key to species found in the study region is provided.